Controls on the shuttling of manganese over the northwestern Black Sea shelf and its fate in the euxinic deep basin. (15th March 2020) - Lenstra, W.K.; Séguret, M.J.M.; Behrends, T.; Groeneveld, R.K.; Hermans, M.; Witbaard, R.; Slomp, C.P.
Abstract: Manganese (Mn) is an essential micronutrient for phytoplankton and its cycling interacts with that of iron (Fe). Continental shelf sediments are a key but poorly quantified source of Mn to marine waters. In this study, we investigate Mn release from shelf sediments, its lateral transport ("shuttling") in the oxic water column over the northwestern Black Sea shelf and its fate in the adjacent euxinic deep basin. We find a high release of Mn from organic-rich, bioirrigated coastal sediments, but negligible mobilization and release of Mn from sediments in offshore shelf regions, because of a low input of organic matter. Most Mn in the water column is present in dissolved form. We suggest that this dissolved Mn is released from coastal sediments and subsequently transported offshore through physical processes. Surface sediments at open shelf and shelf edge stations are highly enriched in Mn when compared to coastal and deep basin stations. Only part of the surface enrichment can be explained by oxidation of porewater Mn. The remainder of this enrichment is likely the result of oxidative removal of dissolved Mn from the water column and deposition as Mn oxides. Using X-ray spectroscopy we show that Mn in surface sediments in this area predominately consists of Mn(IV) oxides (phyllo- and/or tectomanganates). A key difference between Mn versus Fe shuttling is the form in which the metal is transported: while dissolved Mn dominates in the water column over the shelf, most Fe is present in particulate form. Sediment trap data indicate that the vertical transport of both Mn and Fe through the euxinic water column is correlated and is associated with the sinking flux of biogenic particulate matter following the spring and fall phytoplankton blooms. In the sediments of the euxinic basin, Mn is enriched when compared to a detrital Mn background and its burial correlates with that of Fe. This suggests that Mn could be incorporated in pyrite in the euxinic water column. Our results highlight the critical role of organic matter input as a driver of Mn and Fe shuttling over the Black Sea continental shelf and particulate matter as the carrier of Mn and Fe into the euxinic basin.